Crash & burn - Gardner, Lisa (New York, New York : Dutton, 2015)
After surviving a car accident, Nicole Frank enlists the help of Boston police officer Sergeant Wyatt Foster to find a missing girl. The deeper Wyatt digs, the more concerned he becomes, because it turns out, in the past few months, Nicky has suffered from more than one close accident.
A novel.
Keywords: Police -- Massachusetts -- Boston -- Fiction; Traffic accident victims -- Fiction; Attempted murder -- Fiction; Warren, D. D. (Fictitious character) -- Fiction; Boston (Mass.) -- Fiction; Psychological fiction; Mystery fiction; Suspense fiction